Interaction and interdependency between actors to follow-up on performance auditing issues - Sarimah Umor; Zarina Zakaria; Noor Adwa Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2020)
The present study investigates the current state of actual condition that occurs when various actors interact and depend upon one another in resolving performance auditing issues through effective follow-up practice. The present research present findings from semi structured interviewed data involving 55 interviewees. An interpretive approach that is based on qualitative methods was employed to provide insight into the topic under study. Instead of interaction between auditor and auditees, the present study suggests that the regulator and media are among the actors that need to be strongly considered in the follow-up practice. In the case of regulators, it was discovered that earlier information in relation to performance auditing issues requested by regulator was mainly intended to secure availability of particular important evidence as well as to speed up further investigation and action by the regulator. However, this would not necessarily result in greater interaction with regulator, due to the embargo provision of Auditor General (AG) report until the report is tabled in Parliament. Meaning that, the information needs to be secure in terms of confidentiality before the tabling. Therefore, these shortcomings or challenges need to be addressed by the right authority. More so, in the case of media, policy makers often do not realize the rise of the media in shaping the people’s views and influencing the conduct of actors in the network. Besides this, lack of interaction with media may also expose the inability of the government agencies to respond according to current trend and challenges. Follow-up for the resolution of an audit issue in reality may not be solved by the auditee themselves or one party alone. Hence, the need for reliance on other parties considered important regardless of the nature of interdependent, either direct or indirect and formal or informal. Interaction and interdependent between many actors are inevitable in the co-evolving era of postmodern network society. It means that there is an urgent need for deliberation process, value conflicts and the resolution of difficult issues through various autonomous interdependent actors. This is one of the first studies that explores the nature and extent of actors’ interaction and interdependency in follow-up on performance auditing issues in public sector audit field.